Modeling and identification of combined effects of pulsating inlet temperature and use of hybrid nanofluid on the forced convection in phase change material filled cylinder - Selimefendigil, Fatih; Öztop, Hakan Fehmi (Elsevier, 2021)
Effects of pulsating heat transfer fluid temperature and hybrid nano-additive inclusion in the base fluid are numerically studied for laminar forced convection through a phase change material embedded thermo-fluid system with finite element method. Effects of different values of Reynolds number (between 250 and 1000), amplitude (between 0 and 0.05) and frequency (Strouhal number between 0.01 and 0.5) of pulsating inlet temperature, nanoparticle volume fraction of hybrid particles (between 0 and 0.02) on the dynamic features of the system with performance characteristics are analyzed. It is observed that the phase change material onset temperature becomes oscillating with drastically reduction of full completion time as the Reynolds number and amplitude of pulsation are increased. The amount of reduction in the full phase transition is 63% when cases at Re=100 to Re=400 are compared. When lowest and highest amplitude configurations are compared, 62% reduction in the complete phase transition time is observed while the impact of frequency is marginal at higher frequencies. When the hybrid nanoparticles are introduced in the base fluid, transition time and dynamic features of onset temperatures are affected. Successful results that capture the dynamic behavior of the phase change embedded thermal system is achieved with a nonlinear dynamic system modeling approach. (c) 2021 Taiwan Institute of Chemical Engineers. Published by Elsevier B.V. All rights reserved.
Keywords: Phase change material; Hybrid nanofluid; Pulsating; System identification; Finite element method